Formulation and Evaluation of Theophylline Sustained Release Tablet using Lasianthera africana gum - Akpabio, E.I.; Ekong, U. S.; Uwah, T. O.; Ekpa, E. D.; Ubulom, P. M. E.; Jacobs, G. E.; Fred, M. E. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
The aim of this study was to evaluate the potential of Lasianthera africana gum as sustained release matrix for the formulation of theophylline tablet and the effect of this polymer on the physical properties and drug release from the tablets. The polymer was used alone and in binary combination with Guar gum at the concentration level of 20% w/w. The theophylline granules were prepared by the wet granulation method. The micromeritic and flow propert ies of the prepared granules such as bulk density (BD), tapped density (TD), flow rate, Carr’s compressibility index (CI), Hausner’s quotient (HQ) as well as angle of repose (AR) were evaluated using standard methods. The compressed tablets were assessed for weight uniformity, crushing strength, friability, thickness, diameter and uniformity of content. The dissolution profile of the theophylline sustained release tablets was assessed in simulated gastric fluid without the enzyme for a period of 8 h at an agitation rate of 50 rpm and a temperature of 37 ±0.5ºC. Drug release was analyzed spectrophotometrically at wavelength of 271nm using (UNICO-spectrophotometer, UV-2100PC Shanghai Instrument Co., Ltd., China). In order to investigate the release kinetics the data obtained from the in vitro dissolution studies were fitted into various kinetic models which include Zero order, First order and Higuchi. The mechanism of release was further ascertained by fitting the data of the drug release into the Korsemeyer-Peppas equation. The bulk density, tapped density, flow rate, Carr’s inde x, Hausner’s ratio and angle of repose ranged from 0.37 g/cm3 to 0.40 g/cm3, 0.53 to 0. 58 g/cm3, 4.65 to 6.90 g/s, 25.3 to 33.9 %, 1.35 to 1.52, 33.60 to 42.70, respectively. The crushing strength ranged from 5.83 kg/f to 7.07 kg/f, friability ranged from 0.768 % to 0.910 %, diameter for all the batches was uniform (12.51mm), thickness ranged from 2.48 mm to 2.51 mm, while values for content uniformity ranged from 99.17 % to 99.26 %. The two gums sustained the release of theophylline up to 8 h. The release of theophylline followed zero order kinetics via non-Fickian transport.